PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY LEARNING BERBASIS LESSON STUDY FOR LEARNING COMMUNITY PADA MATERI HUKUM DASAR KIMIA TERHADAP HASIL BELAJAR SISWA SMA PERTIWI 1 PADANG - Liza Widyaningrum; Andromeda Andromeda (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
The basic laws of chemistry are one of the materials that are difficult for students to understand because they are abstract, concrete and mathematical. Therefore, it is necessary to choose the right learning model for basic chemical law material to improve students' understanding and involvement in the learning process. Guided Inquiry Learning (GIL) is a type of learning strategy that can increase student participation. In this case, an effective learning system can be applied in improving the quality of learning with the GIL model, the learning system is LSLC (Lesson Study for Learning Community). This research method is a quasi experiment with a research design of Nonequivalent control group design. The data obtained are normally distributed and the variance is homogeneous. Then the hypothesis test carried out is the t-test. obtained t count > t table value so it is concluded that the learning outcomes using the LSLC-based GIL learning model (experimental class) are higher than the control class.